The Rising Importance of Proton Magnetic Resonance Spectroscopy in the Diagnosis of Selected Neurodegenerative Diseases of the Brain - Szmyt, Katarzyna; Superson, Maciej; Wilk-Trytko, Klaudia; Szymańska, Katarzyna; Walczak, Kamil; Samojedny, Sylwia; Mika, Wiktoria; Krasnoborska, Julia; Zarębska, Julia (Journal of Education, Health and Sport, 2024)
Introduction: Neurodegenerative diseases pose a significant diagnostic challenge due to the increasing elderly population and the rising prevalence of these conditions. State of Knowledge: Differential diagnosis among these diseases is particularly challenging; thus, numerous clinical trials have been conducted to identify markers that could facilitate accurate disease diagnosis. Among various diagnostic approaches, imaging techniques play a crucial role, especially magnetic resonance imaging (MRI), which includes advanced modalities such as proton magnetic resonance spectroscopy (¹H-MRS). ¹H-MRS offers a non-invasive assessment of neurometabolite profiles, providing critical information that aids in precise diagnosis. Conclusions: With ongoing clinical trials, the importance of ¹H-MRS in diagnosing neurodegenerative diseases continues to grow. This paper reviews the results of recent and relevant clinical trials examining changes in ¹H-MRS in the most prevalent neurodegenerative diseases.